A brief review: security issues in cloud computing and their solutions - Iqbal Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Cloud computing is an Internet-based, emerging technology, tends to be prevailing in our environment especially in the field of computer sciences and information technologies which require network computing on large scale. Cloud Computing is a shared pool of services which is gaining popularity due to its cost, effectiveness, avilability and great production. Along with its numerous benefits, cloud computing brings much more challenging situation regarding data privacy, data protection, authenticated access, Intellectual property rights etc. Due to these issues, adoption of cloud computing is becoming difficult in today’s world. In this review paper, various security issues regarding data privacy and reliability, key factors which are affecting cloud computing, have been addressed and also suggestions on particular areas have been discussed.